2019
DOI: 10.1177/1833358319864734
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the information quality and usability of My Health Record within a health literacy framework: What’s changed since 2016?

Abstract: Background: This study examined the health literacy demands of My Health Record (MyHR) in the context of preparing for a government-announced opt-out system by repeating two studies of health information and usability conducted in 2016. Objective: To examine whether Australia’s MyHR meets the information and usability needs of people at risk of low health literacy and changes since 2016. Method: Content analysis: Informed by the 2016 methods and findings, measures of information quality, themes and target audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…However, Walsh et al [19] analysed the content of the MyHR system and contradicted that finding. The authors hold the view that relevant information about how patients can engage with healthcare professionals was not provided.…”
Section: Coordination Of Carementioning
confidence: 99%
See 3 more Smart Citations
“…However, Walsh et al [19] analysed the content of the MyHR system and contradicted that finding. The authors hold the view that relevant information about how patients can engage with healthcare professionals was not provided.…”
Section: Coordination Of Carementioning
confidence: 99%
“…Several authors [8,10,[15][16][17][18][19] in this area discussed both positive and negative issues of the system and information quality and access. The positive outcomes are that the health information stored in several repositories can be accessed by one system through an interface that shows relevant information on the first website page, which eliminates the reliance on patients remembering facts about their health during medical appointments.…”
Section: Health Information Quality and Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, another group of researchers used both methods [14]. In their subsequent study, the researchers [18] reported that the HLO checklist "was easier to use and returned more specific results than the second heuristic set" (i.e., Evidence-Based Heuristics), with two exceptions which they integrated into their inspection checklist. We categorized these findings into strengths and weaknesses for each tool and examined them for commonalities.…”
Section: Comparisonmentioning
confidence: 99%